Archives in 3D - Cardin, Martine (Archivaria, 2001)
This article examines the characteristics of archives (records) susceptible to modification by changes in context. After briefly defining the notion of context, the author proposes a complex analytical model, taking into account what archives are, what they do, and what they represent for their creators. By applying such a model to a traditional definition of archives, the author can identify the physical, functional, andsymbolic characteristics of archives and explore how they have been conditioned by contexts of recording, communication, and memory making. Résumé Le présent article examine les effets que peuvent avoir divers contextes sur les caractéristiques des documents d’archives. Après avoir brièvement défini la notionde contexte, l’auteure propose un modèle d’analyse complexe tenant simultanément compte de ce que les archives sont, de ce qu’elles font et de ce qu’elles représentent pour leurs producteurs. L’application d’un tel modèle sur la définition traditionnelledes archives permet à l’auteure d’identifier des caractéristiques physiques, fonctionnelles et symboliques de la production documentaire et de voir comment ces dernières sont plus ou moins conditionnées par des contextes de consignation, de communicationet de mémoire.